2008
DOI: 10.1080/09638230701505996
|View full text |Cite
|
Sign up to set email alerts
|

Patients' core experiences of hospital treatment: Wholeness and self-worth in time and space

Abstract: Introduction: Few studies have addressed staff and patient experiences of the therapeutic milieus at psychiatric institutions from a learning perspective. The purpose of this study was to gain more knowledge about the meaning and value the psychiatric institution may have as a place for learning in time and space for patients with various mental disorders, and how the staff may contribute in the learning processes of the patients. We were especially interested in studying patients' experiences by taking part i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
45
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 77 publications
0
45
1
Order By: Relevance
“…Similar results were reported by Shattell et al (2008) and Stenhouse (2011), who showed how patients turned to each other for support when nurses were unavailable. Borge and Fagermoen (2008) found positive effects for patients who described spending time with fellow patients as valuable. Meeting people who struggled with similar problems made them feel less lonely and somewhat relieved.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Similar results were reported by Shattell et al (2008) and Stenhouse (2011), who showed how patients turned to each other for support when nurses were unavailable. Borge and Fagermoen (2008) found positive effects for patients who described spending time with fellow patients as valuable. Meeting people who struggled with similar problems made them feel less lonely and somewhat relieved.…”
Section: Discussionmentioning
confidence: 85%
“…Features, such as communication, both verbal and written, between nursing staff and patients were important key components for the patient's feelings of safety. Borge and Fagermoen (2008) also reported that patients on a psychiatric ward were very conscious of who of the nursing staff they had contact with and preferred nursing staff that took them seriously.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…First, the two domains showing change over time, Self-esteem and Health, may have been responsive to aspects of the therapeutic milieu (Norton, 2004;Borge & Fagermoen, 2008), since patients are treated for medical problems and engage in physical activity, arts and craft s, psychoeducation, and other groups. Second, patients' subjective life satisfaction may be lower, say for self-esteem, immediately following admission to the hospital and improved with time, although these participants' mean scores remained in the "low" range at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…These qualities are also called "befriending" and seem to be important as a form of social support in order to keep up an active engagement of patients in mental health care (Milne, Wharton, James, & Turkington, 2006). These features engender feelings of recognition, cooperation, and personal value in patients (Borge & Fagermoen, 2008;Borge & Hummelvoll, 2008;Scaturo, 2010;Stickley & Freshwater, 2009). A good learning climate, created through interdisciplinary collaboration, and its environmental impact, can be key features in the individual patient's learning process and can be understood from a sociocultural perspective.…”
mentioning
confidence: 98%